Dates and Barley Antioxidant Staple Foods In The Makkan Society Diet (609-622 A.D.) - Nurul Mukminah Zainan Nazri; Norhasnira Ibrahim (Universiti Sains Islam Malaysia, 2024)
Ulum Islamiyyah: Malaysian Journal of Islamic Sciences Volume 36 Issue 1 Page (1-7)